Violence Case Reporting and Information Service Application to Support the PPKPT Task Force Program - Imam Ajie Pradana; Arfhan Prasetyo; Instianti Elyana; Rangga Ramadhan Saelan (Journal of Information System, Applied, Management, Accounting and Research, 2026)
The increasing incidence of violence within higher education institutions necessitates the implementation of a responsive mitigation system in accordance with Permendikbudristek Nomor 55 Tahun 2024. This study aims to design a web-based information service application for the Task Force for the Prevention and Handling of Violence in Higher Education (PPKPT) at Universitas Nusa Mandiri. The development process adopts a structured approach consisting of several stages, namely planning, design, programming, and testing. The Extreme Programming (XP) method is implemented to provide flexibility in mapping various forms of violence. The system integrates key features, including a secure online complaint form, educational content and activity publication, as well as policy information services. System testing is conducted through performance testing using Apache JMeter, User Acceptance Testing (UAT), and System Integration Testing (SIT). The performance testing results indicate an average access success rate of 90%, with an average response time of 248 milliseconds. The UAT results confirm that the system is capable of facilitating anonymous and efficient reporting. This study concludes that the application enhances the accessibility of Task Force services while ensuring the security of reporters’ data within the campus environment, thereby improving the overall reach and effectiveness of PPKPT services.